Non-viral gene delivery and bone marrow cells in inner ear repair - Tan, Brian Tiong Gee (2009)
Hearing impairment is the most common sensory deficit in humans and degeneration of auditory hair cells is the major cause of this deficit. Over the past ten years, gene therapy has emerged as a promising approach in the treatment of hearing loss through identification of individual genes and proteins involved in hearing and development of various methods of delivery to the cochlea. Many studies employed the use of viral-mediated gene transfer and delivery through cannulation of the cochlea. Results are encouraging; however the use of viral vectors as gene delivery vehicle (host immunological response) and direct cannulation (surgical trauma) of the cochlea still has potential risks and raises major safety concerns. Hence, the objective of this work is to address these concerns through exploring 1) the use of a non-viral vector, polyethylenimine (PEI) as gene delivery vector and studying 2) the role of the host's intrinsic bone marrow cells' (BMCs’) in the restoration process after deafening. Various delivery methods were compared and assessed to select the optimal method for non-viral vector gene delivery. The rank order of the various delivery routes based on transfection efficacies was - osmotic pump infusion > cochleostomy > round window membrane inoculation > Gelfoam method. Hence PEI-eGFP was introduced with sustained delivery into guinea pig cochleae using an osmotic pump and examined for transgene expression. PEI-mediated gene transfer was demonstrated and the infused cochleae maintained intact cellular and tissue architecture with the absence of inflammation. PEI’s relatively lower transfection efficiency limits it potential when compared to viral counterparts; however, we have shown that sustained release of the vector solution improved PEI’s transfection efficiency and offers a solution to compensate for non-viral vectors’ relatively low transfection efficiency. These findings indicate that PEI is able to transfect the cochlea in vivo and present an alternative for cochlea gene therapy.